2021
DOI: 10.1002/net.22045
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourced logistics: The pickup and delivery problem with transshipments and occasional drivers

Abstract: This article considers a setting in which a courier, express, and parcel service provider operates a fleet of vehicles with regular drivers (RDs) to ship parcels from pickup to delivery points. Additionally, the company uses a platform where occasional drivers (ODs) offer their willingness to take on requests that are on or near the route they had originally planned. There exist transshipment points (TPs) to better integrate these ODs. ODs or RDs may transfer load at these predetermined TPs. The problem is mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The vehicle routes are periodic and static, while the parcel routes are determined dynamically based on capacity consideration and the location of the vehicles when a parcel arrives. Another approach is to opportunistically outsource the transportation tasks between SPs in the network to drivers who follow their regular trips and are ready to collect parcels and drop them somewhere later on their planned route in exchange for a monetary reward [78, 93].…”
Section: Urban Micro‐consolidation Centersmentioning
confidence: 99%
“…The vehicle routes are periodic and static, while the parcel routes are determined dynamically based on capacity consideration and the location of the vehicles when a parcel arrives. Another approach is to opportunistically outsource the transportation tasks between SPs in the network to drivers who follow their regular trips and are ready to collect parcels and drop them somewhere later on their planned route in exchange for a monetary reward [78, 93].…”
Section: Urban Micro‐consolidation Centersmentioning
confidence: 99%
“…To increase the flexibility of delivery systems, some studies focus on the PDP with transshipments. Voigt et al [21] propose the PDP considering the possibility of transshipments between drivers for crowdsourced logistics in last-mile delivery, and develop a heuristic solution approach based on ALNS to solve it. Wolfinger [22] addresses a PDPTW with split loads and transshipments and constructs an arc-based mixed integer model, which is solved by the large neighbourhood search (LNS) algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crowdsourced delivery applies the concept of crowdsourcing to logistics [6]. According to the structure proposed by Nourinejad and Roorda [7], there are two types of methods for dealing with the evaluation of crowdsourced delivery in last-mile logistics: centralized and decentralized.…”
Section: Literaturementioning
confidence: 99%
“…us, compensation schemes were included and discussed in the context of the PDPOD by Dahle et al [16]. In the same research stream as the PDPOD, the impact of allowing for task transfer between ODs was investigated by Voigt and Kuhn [6]. eir numerical results showed that the introduction of trans-shipment points increased the utilization of ODs and significantly reduced total cost.…”
Section: Centralized System Optimizationmentioning
confidence: 99%
See 1 more Smart Citation